Advances of Machine Design in Italy 2022 - Ceccarelli, Marco; Carbone, Giuseppe; Gasparetto, Alessandro (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint contains a Special Issue of the MDPI journal Machines on Italian advances in mechanism and machines science through a collection of selected papers from the Fourth International Conference of IFToMM Italy, IFIT 2022. The included papers belong to a broad range of disciplines in MMS, with research and design results that can be of interest not only to scholars in the field of MMS and mechanical engineering but also to professionals and even students, broadening their understanding of the problems and solutions under development, mainly, but not only, from the Italian community.